2015
DOI: 10.1007/s11999-015-4246-5
|View full text |Cite
|
Sign up to set email alerts
|

β-Ecdysone Augments Peak Bone Mass in Mice of Both Sexes

Abstract: Background One of the strongest predictors for osteoporosis is peak bone mass. Interventions to augment peak bone mass have yet to be developed. b-Ecdysone (bEcd), a natural steroid-like compound produced by arthropods to initiate metamorphosis, is believed to have androgenic effects and so may be used to augment bone mass. Questions/purposes The purpose of this study was to use both male and female (1) gonadal-sufficient; and (2) -insufficient mice to investigate sex differences in terms of bone development a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Animals are typically young and, in most cases, have not even reached peak bone mass 35,36 . For example, in mice, peak bone mass is reached at ~ 4 months of age; in rats at ~ 9 months of age and in mini pigs, between ~ 2 and 3 years [37][38][39] . While it would be an obvious advantage to use animals whose skeletal age aligned with the intended patient population, this is very rarely achieved because the cost associated with housing large animals until they have reached peak bone mass (or older) is prohibitive.…”
Section: Discussionmentioning
confidence: 99%
“…Animals are typically young and, in most cases, have not even reached peak bone mass 35,36 . For example, in mice, peak bone mass is reached at ~ 4 months of age; in rats at ~ 9 months of age and in mini pigs, between ~ 2 and 3 years [37][38][39] . While it would be an obvious advantage to use animals whose skeletal age aligned with the intended patient population, this is very rarely achieved because the cost associated with housing large animals until they have reached peak bone mass (or older) is prohibitive.…”
Section: Discussionmentioning
confidence: 99%
“…Due to possible androgenic and growth-stimulating effects, 20β-OH-ecdysone has been examined on the subject of acceleration of bone mass augmentation. Mice treated with 20β-OH-ecdysone at a dose of 0.5 mg/kg for three weeks with a frequency of 5 times per week showed an increase of strength and volume of both trabecular and cortical bones up to 0.88 ± 0.03 and 0.79 ± 0.2 ( p < 0.05) in male and female animals for trabecular bone volume, and up to 15 ± 0.3 and 12 ± 0.5 ( p < 0.05) in male and female animals for cortical bone volume [ 120 ]. Although the bone mass augmentation is pre-determined by gender-specific hormonal background and, specifically, by estrogen receptors loading, authors demonstrated that 20β-OH-ecdysone provides equal impact regardless of the gender feature ( Table 1 ).…”
Section: Dietary Sterols In Sportmentioning
confidence: 99%
“…The protective effect of 20β-OH-ecdysone against the loss of bone volume and density due to competing interaction with glucocorticoids and inhibition of stromal cells autophagy has been observed in rats who were being implanted with slow-releasing (for 60 days) prednisolone [ 120 ]. Regular treatment with 20β-OH-ecdysone entailed to the elevated level of bone mineralizing surface (up to 43%, p < 0.05) and the increased bone formation at the endocortical surface (up to 213%, p < 0.05).…”
Section: Dietary Sterols In Sportmentioning
confidence: 99%
“…9 β-ecdysone (βEcd), which is found in many plants, is involved in protein synthesis, carbohydrate and lipid metabolism, and immunological modulation. 10 Dai et al 11 reported that βEcd could increase peak bone mass in growing male and female mice. Moreover, it was also found that βEcd could prevent glucocorticoid-induced changes in bone formation, bone cell viability and bone mass.…”
Section: Introductionmentioning
confidence: 99%